A hybrid blockchain overlay for secure and compliant document management and tokenisation in public and enterprise systems - Benjamin Brooks; Luigi Lunardon; Alessio Pagani (Blockchain)
This work presents SOvNet, a blockchain-agnostic hybrid solution that combines the privacy of proprietary systems with the resilience of public blockchains. SOvNet is a private network that publishes cryptographic fingerprints of its data on public blockchains, while aiming to simplify the management of personal data and transactions. The network is maintained by a group of nodes that updates the system status and provides cryptographic proofs of data processing to the network users. Designed for governments and enterprises, SOvNet supports services such as document management, real-world asset digitalisation, and digital payments. It also supports communication between SOvNet instances with minimal user-side overhead. The user interface to interact with SOvNet implements only lightweight operations, allowing for deployment on personal devices, including laptops and smartphones.